Urinary Tract Infection Due to Non-fermentative Gram-Negative Bacilli in Tribhuvan University Teaching Hospital, Kathmandu, Nepal - Yadav, Santosh Kumar; Jha, Uday Kant; Sherchan, Jeevan Bahadur (NUTA Journal, 2020)
Urinary tract infections (UTIs) are the second most common type of bacterial infection of the body affecting humans throughout their lifetime. They are a frequent cause of nosocomial in fection in many hospitals. Therefore, this study was designed to isolate and identify the non-fermentative Gram-negative bacilli (NFGNB) causing UTI in hospitalized patients and determine their antibiotic susceptibility profile. This study was carried in Tribhuvan University Teaching Hospital, Nepal among hospitalized patients. The urine sample was cultured and the antibiotic susceptibility profile of isolated NFGNB was determined by standard microbiological procedures. Among the total of 49 NFGNB isolates, Acinetobacter species (n=21, 42.9%) and Pseudomonas aeruginosa (n=21, 42.9%) were the major isolates and the remaining was Burkholderia cepacia complex (n=7, 14.3%). These isolates were found resistant to commonly used antibiotics. From the present study, it is clear that NFGNB are an important bacterial pathogen capable of producing UTI in hospitalized patients.